1996
DOI: 10.1002/(sici)1096-9861(19960429)368:2<185::aid-cne2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of galanin‐like immunoreactive elements in the brain of the adult lamprey Lampetra fluviatilis

Abstract: Galanin is a brain-gut peptide present in the central nervous system of vertebrates and invertebrates. The distribution of galanin-like immunoreactive perikarya and fibers in the brain of the river lamprey Lampetra fluviatilis (Agnatha) has been studied immunocytochemically by using antisera against rat and porcine galanin. Galanin-like immunoreactive perikarya were seen in the telencephalon and mediobasal diencephalon. In the telencephalon, they were present in the nucleus olfactorius anterior, nucleus basali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 74 publications
(82 reference statements)
4
25
0
Order By: Relevance
“…The distribution of galanin-IR cells in the POA, AH, and hypothalamus has been previously described in adults of several species, including lamprey (Jiménez et al, 1996), sailfin molly Parsons, 1991a, 1991b), turtle (Jiménez et al, 1994), several amphibians (Olivereau and Olivereau, 1992), chicken (Józsa and Mess, 1993), and many mammals including rats (Melander et al, 1986), opposums (Elmquist et al, 1992), gerbils (Ulibarri and Rust, 1996), pigs (Pearson et al, 1996), and primates (Kordower et al, 1992) including man (Gai et al, 1990). In some instances the distribution of galanin-IR cells in the POA or hypothalamus has been shown to be sexually dimorphic.…”
Section: Discussionmentioning
confidence: 97%
“…The distribution of galanin-IR cells in the POA, AH, and hypothalamus has been previously described in adults of several species, including lamprey (Jiménez et al, 1996), sailfin molly Parsons, 1991a, 1991b), turtle (Jiménez et al, 1994), several amphibians (Olivereau and Olivereau, 1992), chicken (Józsa and Mess, 1993), and many mammals including rats (Melander et al, 1986), opposums (Elmquist et al, 1992), gerbils (Ulibarri and Rust, 1996), pigs (Pearson et al, 1996), and primates (Kordower et al, 1992) including man (Gai et al, 1990). In some instances the distribution of galanin-IR cells in the POA or hypothalamus has been shown to be sexually dimorphic.…”
Section: Discussionmentioning
confidence: 97%
“…10D,E). The possible origin of these galanin-ir fibers was not determined because none of the galanin-ir brain nuclei reported in a previous study of the river lamprey (Jiménez et al, 1996) corresponds with the efferent nuclei demonstrated by DiI application to the parapineal organ.…”
Section: Immunocytochemistry Of the Parapineal Organmentioning
confidence: 98%
“…The other brains were cryoprotected with 30% sucrose, frozen with liquid nitrogen, sectioned (15-µmthick) in the same planes on a cryostat, and processed according to the immunoperoxidase technique. Briefly, sections were incubated with one of the primary antisera raised in rabbits against GABA (Chemicon, Temecula, CA; Affinity, Mamhead, U.K.; or Sigma; Pombal et al, 1997; dilution, 1:1,000 to 1:2,000), 5-HT (Zhang et al, 1996; dilution 1:1,000), SP ; dilution 1:2,000), CR (7696, Swant, Bellinzona, Switzerland;Schwaller et al, 1993; dilution, 1:1,000), NPY (Sigma; dilution, 1:600), or galanin (Jiménez et al, 1996; dilution 1:1,500). They were subsequently incubated with goat anti-rabbit (Dakopatts, Glostrup, Denmark; dilution, 1:60) and rabbit peroxidase-antiperoxidase complex (Dakopatts; dilution, 1:300).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…It was first isolated and characterized from the porcine intestine (Tatemoto et al 1983). Many studies have demonstrated the distribution of GAL-like immunoreactive (ir) neurons and fibers in the brain of mammals (Skofitsch and Jacobowitz 1985;Melander et al 1986;Levin et al 1987;Palkovits et al 1987;Blasco et al 1989;Gaymann and Martin 1989;Gentleman et al 1989;Walker et al 1989;Kordower and Mufson 1990;Meister et al 1990;Elmquist et al 1992;Kordower et al 1992), birds (Józsa and Mess 1993), reptiles (Jiménez et al 1994), amphibians (Wolfbauer and Skofitsch 1989;Lázár et al 1991;Olivereau and Olivereau 1992), bony and cartilaginous fish (Batten et al 1990a(Batten et al , 1990bParsons 1991a, 1991b;Holmqvist and Ekström 1991;Olivereau 1991a, 1991b;Vallarino et al 1991;Holmqvist and Carlberg 1992;Yamamoto et al 1992;Magliulo-Cepriano et al 1993;Anglade et al 1994;Prasada Rao et al 1996;Rodríguez-Gómez et al 2000;Jadhao and Meyer 2000), and the sea lamprey (Jiménez et al 1996). Furthermore, the distribution of GAL and its receptor-binding sites in the brain and pituitary are well documented in the rat (Meister and Hökfelt 1992), sea bass (Moons et al 1991), and Atlantic salmon (Holmqvist and Carlberg 1992).…”
Section: Introductionmentioning
confidence: 99%